Impact of stability on the performance of Persian Gulf Pro League football clubs - Hosseini Keshtan, M.; Fazel Bakhsheshi, M.; Zareian, H.; Reihani, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The objective of this study was to determine the impact of stability/instability on the performance of Persian Gulf Pro League football clubs. All the clubs that had participated in more than 3 seasons of the last 17 seasons (2001-2019) of the Persian Gulf Pro League were analyzed in this study (n=26). The performance of each team (improvement or worsening in ranking) and their stability were analyzed year after year in the period 2001-2019. The stability was divided in four components: CEO, head coach, players and club. The statistical analysis was performed with the software SPSS. Stability significantly (p<0.05) increased performance and instability significantly (p<0.05) decreased performance of the clubs in the four components studied: CEO, head coach, players and club. Therefore, it is expected that the results of this study encourage Iranian football clubs to increase their stability.